ENHANCEMENT OF METHANE OXIDATION WITH EFFECTIVE METHANOTROPHIC MIXED CULTURES - Barasarathi, Jayanthi; P., Agamuthu (Malaysian Journal of Science, 2011)
The emission of CH4 from landfill is ranked third among the anthropogenic CH4 sources and ranged between 19-40Tg/yr. The Microbial oxidation of landfill methane plays a significant role in reducing the emissions to the atmosphere. This study was carried out to the investigate the impact of several parameters on methane(CH4) oxidation, using compost as biocover. Addition of dedicated methanotrophic bacterial cultures was also included.. Experiments with different concentrations of methanotrophic mixed cultures ranging from 2.33X 107 CFU/g to 11.33X 107 CFU/g showed that the highest oxidation rate with addition of 5.33 X 107 CFU/g was 4.166 X 103 ugg-1 h -1 . Experiments with different incubation temperature showed that highest oxidation rate of 4.166 X 103 ugg-1 h -1 was at 35 C. Similar oxidation rates were obtained with the addition of mixed culture at 60% moisture content. The highest bacterial count was obtained at 35 C at 12.33 X 107 CFU/g while lowest was at 45 C. The moisture at 60% showed the highest bacterial count at 10.66 X 107 CFU/g whereas 30% moisture showed the lowest count at 3 X 107 CFU/g. From this study we concluded that the addition of methanotrophic mixed culture gave a significant increase in methane oxidation compared to the control at the optimal temperature and moisture content. (Key words: methane oxidation rate, methanotrophic mixed culture, compost, Biocover)